1996
DOI: 10.1046/j.1365-2265.1996.673496.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid 5α‐reductase 2 deficiency: virilization in early infancy may be due to partial function of mutant enzyme

Abstract: Male pseudohermaphroditism due to steroid 5 alpha-reductase deficiency is the consequence of mutations in the gene encoding the type 2 isoenzyme. Most (60%) affected subjects have homozygous mutations, and the remainder are compound heterozygotes or presumed compound heterozygotes. We report an Italian subject with phenotypic and endocrine features of 5 alpha-reductase 2 deficiency who is homozygous for a substitution mutation (H231R). Although close consanguinity is not present, genealogical data demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
1
17
0
2
Order By: Relevance
“…In our study, the enzymatic activity was retained in about 40% with the p.G203S mutation. It was reported that the SRD5A2 missense mutation retaining 3–15% of enzymatic activities was associated with partial male external genitalia [20]. Therefore, the p.G203S mutation was also associated with masculinization of the external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the enzymatic activity was retained in about 40% with the p.G203S mutation. It was reported that the SRD5A2 missense mutation retaining 3–15% of enzymatic activities was associated with partial male external genitalia [20]. Therefore, the p.G203S mutation was also associated with masculinization of the external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Mais de 40 mutações diferentes já foram descritas, compreendendo em sua maioria mutações de ponto do tipo missense ou nonsense e, mais raramente, mutações que afetam o mecanismo de splicing, mutações frameshift (que alteram a fase de leitura) ou deleções completas do gene (8,13,(15)(16)(17)(18)(19)(20). Segundo Thigpen e cols.…”
Section: Discussionunclassified
“…A freqüência elevada de heterozigotos compostos sugere que a freqüência de portadores na população em geral pode ser alta, o que explicaria a recorrência de determinadas mutações em afetados não consangüí-neos. Por outro lado, a recorrência de mutações idênti-cas em diferentes grupos étnicos e de regiões geográfi-cas distintas tem sugerido a existência de regiões hot spots no gene; em outros casos, mutações similares dentro do mesmo grupo étnico seriam derivadas de mutações presentes em ancestrais comuns (8,13,21).…”
Section: Discussionunclassified
“…These cases were all considered to be girls at birth (6,8,10). The mutation has even been reported in a heterozygous form in two cases regarded as presumed compound heterozygotes, one in an Afro-American and the other in an American Caucasian proband (1).…”
Section: Resultsmentioning
confidence: 99%